Design of Deep-Sea Acoustic Vector Sensors for Unmanned Platforms - Qindong Sun; Lianglong Da (Journal of Marine Science and Engineering)
To meet the critical need for compact, multifunctional acoustic vector sensors on deep-sea unmanned platforms such as acoustic profiling buoys and underwater gliders, we have developed a novel composite resonant acoustic vector sensor capable of large-depth operations. The sensor innovatively integrates the sound pressure channel and the vector channel, and utilizes the conjugate cross-spectrum between them to effectively reduce the isotropic noise, enhance the detection of weak signals from ships, and make up for the shortcomings of a single sound pressure channel and a vector channel. Certified to function reliably at depths up to 1500 m, field sea trials confirm its efficacy in deep-sea deployments, capturing essential marine environmental noise data. Key analysis during sea trials focused on marine ambient noise levels captured at frequencies of 65 Hz, 125 Hz, 315 Hz, 400 Hz, and 500 Hz, correlating these with changes in depth. The test results revealed the following insights: (a) At the same depth, the marine environmental noise level increases as the frequency decreases; (b) At the same frequency, the marine environmental noise level decreases with increasing depth; (c) Under favorable deep-sea conditions, the marine environmental noise level reaches 55 decibels (dB) at 500 Hz; (d) Noise levels tend to increase at various frequencies when surface ships are in proximity. These findings underscore its significant potential for enhancing deep-sea acoustic surveillance and exploration.